Ascorbic acid status in children with malnutrition - Taş, Mualla; Özalp, İmran; Müftü, Yunus; Say, Burhan (The Turkish Journal of Pediatrics, 1974)
Leucocyte ascorbic acid concentration and plasma ascorbic acid levels were measured, and the correlation was determined in 42 children with malnutrition, 15 children with bronchopneumonia, and in 20 healthy children.Children with malnutrition had significantly lower leucocyte and plasma ascorbic acid levels than those of the controls. (P< 0.05).No correlation was found between the leucocyte ascorbic acid concentration and plasma ascorbic acid levels in the control group. The correlation between these two variables was significant in children with malnutrition. This positive correlation finding, together with decreased ascorbic levels in leucocytes and plasma, may be considered as a criteria indicating an ascorbic acid deficit in malnourished children.